(untitled) (BIRDEM Medical Journal, 2021)
Acute pulmonary embolism is one of the most common causes of vascular death after myocardial infarction and cerebrovascular accidents. It usually presents with severe chest pain and shortness of breath and occasionally occurs in the background of deep vein thrombosis. A 32-year-old male presented with swelling of left lower limb and shortness of breath. Subsequent investigations revealed that he developed DVT of left lower limb and pulmonary embolism. However, in general, if left untreated, pulmonary embolism is associated with an overall mortality of up to 30 percent compared with 2 to 11 percent in those treated with anticoagulation. Early diagnosis by D-dimer, computed tomograpgy pulmonary angiogram and doppler study of the left lower limb and prompt intervention through low molecular weight heparin and rivaroxaban led to a successful outcome in our case. Birdem Med J 2021; 11(2): 142-144